Efficacy of Low-Dose Paroxetine for the Treatment of Hot Flushes in Surgical and Physiological Postmenopausal Women: Systematic Review and Meta-Analysis of Randomized Trials - Gaetano Riemma; Antonio Schiattarella; Marco La Verde; Giuseppina Zarobbi; Simone Garzon; Gaspare Cucinella; Gloria Calagna; Domenico Labriola; Pasquale De Franciscis (Medicina, 2019)
Background and Objectives: Hot flushes and sleep disturbances are the most common vasomotor symptoms (VMS) reported by postmenopausal women. Hormonal treatment is to date referred to as the gold standard approach but not suitable for all the patients. Alternative treatments are needed in case of a contraindication to menopausal hormone therapy (MHT), adverse side effects, and poor compliance. Paroxetine salt is the only nonhormonal medication approved by the US Food and Drug Administration for the management of VMS. Nonetheless, few trials with low consensus are available about this topic. In this review, we aimed to evaluate the efficacy of low-dose paroxetine therapy in the treatment of vasomotor hot flushes and night sleep disturbances in postmenopausal women. Materials and Methods: We performed an electronic search from the beginning of all databases to July 2019. All results were then limited to a randomized trial. Restrictions for language or geographic location were not utilized. Inclusion criteria were randomized clinical trials of physiological or surgical postmenopausal women experiencing hot flushes and sleep disturbances who were randomized to either low-dose paroxetine or placebo (i.e., formulations without active ingredients). The primary outcome evaluated was the mean weekly reduction of hot flushes. Results: Five randomized clinical trials, including 1482 postmenopausal women, were analyzed. Significant heterogeneity (I2 = 90%) between studies was noted. Hot flushes episodes were significantly reduced in the treatment arm compared to placebo (mean difference (MD) −7.97 [−10.51, −5.92] episodes/week). Results on the improvement on sleep were limited by being reported in only two studies; however, no significant reduction of night-time awakenings was observed (MD, −0.40 awakenings/night [−1.38, 0.58 CI]). Conclusions: Low-dose paroxetine is an effective treatment for vasomotor menopause symptoms, including hot flushes.